Role of Cooperative for Sustainable Women Empowerment in Birendranagar Municipality - Rawat , Khem Raj (Journal of Entrepreneurship & Management Studies, 2024)
The research investigates the role of cooperatives in promoting sustainable women’s empowerment, addressing gaps in knowledge about their impact, particularly in low-income countries. It emphasizes the multifaceted nature of empowerment and explores how economic, socio-cultural, entrepreneurial, leadership skills, advocacy, and awareness dimensions intersect. Through correlation and regression analyses, significant positive associations between Sustainable Women Empowerment (SWE) and these dimensions are revealed, highlighting the importance of considering them collectively in empowerment initiatives. The research employs a positivist research philosophy and adopts a descriptive and causal research design to address the research problem through data collection and analysis systematically. Primary data collection involves structured questionnaires distributed among women shareholders/members of a cooperative organization in Birendranagar Municipality. A sample size of 408 respondents is determined through convenience sampling. Specifically, the regression analysis demonstrates that Economic Empowerment (EE), Socio-cultural Empowerment (SCE), Advocacy and Awareness (AnA), Entrepreneurship Empowerment (EntE), and Leadership Skills Empowerment (LSE) significantly influence SWE. For instance, the coefficients for EE, SCE, AnA, EntE, and LSE are 0.205, 0.226, 0.116, 0.165, and 0.183, respectively, indicating the estimated change in SWE associated with a one-unit increase in each respective predictor, while holding others constant. These findings have implications for policymakers and stakeholders, suggesting the need for comprehensive interventions targeting multiple empowerment dimensions to foster sustained positive changes in women’s lives and contribute to broader social and economic development goals.